Unusual Presentation of Uncommon Disease: Anorexia Nervosa Presenting as Wernicke-Korsakoff Syndrome—A Case Report from Southeast Asia - Raheel Mushtaq; Sheikh Shoib; Tabindah Shah; Mudasir Bhat; Randhir Singh; Sahil Mushtaq (Case Reports in Psychiatry)
Anorexia nervosa presenting as Wernicke-Korsakoff syndrome is rare. The causes of Wernicke-Korsakoff syndrome are multiple like alcohol abuse, thyrotoxicosis, haemodialysis, severe malnutrition because of gastric carcinoma and pyloric obstruction, hyperemesis gravidarum, and prolonged parenteral feeding. We report a case of anorexia nervosa, who presented with Wernicke's encephalopathy and progressed to Korsakoff's syndrome. Knowledge, awareness, and early intervention of anorexia nervosa by mental health professionals can prevent development of Wernicke-Korsakoff syndrome.